DETERMINANTS OF SUSTAINABILITY ASSURANCE: EVIDENCE FROM ENERGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2021-2024 - Patricia Hezekiah; Kurniawati (Journal of Business And Entrepreneurship, 2026)
Sustainability report assurance (SRA) plays a critical role in enhancing the credibility of ESG disclosures. However, despite expanding sustainability reporting requirements under POJK No. 51/POJK.03/2017, SRA in Indonesia remains voluntary, creating a credibility gap in ESG disclosures. To address this issue, this study examines the effect of corporate governance mechanisms, comprising external mechanisms (institutional ownership and ownership concentration) and internal mechanisms (audit committee and sustainability committee), on sustainability report assurance practices among energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2021 to 2024. It also provides a comparative analysis of assurance statement content between public accounting firms (KAP) and non-accounting providers (non-KAP), revealing substantive differences in standards, scope, and conclusion formats, a contribution that offers practical guidance for stakeholders navigating the evolving assurance landscape. Using a quantitative causal comparative approach and purposive sampling, 52 energy sector companies (208 observations) were analyzed through binary logistic regression in EViews. The findings indicate that institutional ownership has no significant effect on SRA, whereas ownership concentration has a significant negative effect. Conversely, both audit committee meeting frequency, and the presence of a sustainability committee positively drive SRA adoption, with the sustainability committee exhibiting the strongest impact. Furthermore, the comparative analysis reveals substantive differences between KAP and non-KAP providers regarding the standards used, scope, and conclusion formats. Ultimately, internal governance mechanisms are more effective in driving SRA than ownership structures; thus, regulators and companies should prioritize establishing sustainability and active audit committees to enhance sustainability reporting credibility. Conclusively, this study strengthens stakeholder and legitimacy theories by demonstrating how internal governance functions as a critical mechanism for maintaining corporate legitimacy and meeting stakeholder demands.